Various Techniques for the Surgical Treatment of Common Bile Duct Stones: A Meta Review - Abolfazl Shojaiefard; Majid Esmaeilzadeh; Ali Ghafouri; Arianeb Mehrabi (Gastroenterology Research and Practice)
Common bile duct stones (CBDSs) may occur in up to 3%–14.7% of all patients for whom cholecystectomy is preformed. Patients presenting with CBDS have symptoms including: biliary colic, jaundice, cholangitis, pancreatitis or may be asymptomatic. It is important to distinguish between primary and secondary stones, because the treatment approach varies. Stones found before, during, and after cholecystectomy had also differing treatments. Different methods have been used for the treatment of CBDS but the suitable therapy depends on conditions such as patient' satisfaction, number and size of stones, and the surgeons experience in laparoscopy. Endoscopic retrograde cholangiopancreatography with or without endoscopic biliary sphincterotomy, laparoscopic CBD exploration (transcystic or transcholedochal), or laparotomy with CBD exploration (by T-tube, C-tube insertion, or primary closure) are the most commonly used methods managing CBDS. We will review the pathophysiology of CBDS, diagnosis, and different techniques of treatment with especial focus on the various surgical modalities.